Toward a mandatory public e-services in Jordan - Wesam Ibrahaim Mohammad Alabdallat (Cogent Business & Management, 2020)
With the rapid developments in utilizing the popularity of internet, the governments all over the world adopted various e-government projects to provide their services. This paper aimed to investigate how the governmental departments in Jordan can provide mandatory e-services to citizens. It sought to review the recent reality of the e-services provided to receivers especially among citizens by the governmental departments in Jordan. Moreover, it seeks to identify the obstacles that hinder achieving this goal. In order to deal with this issue, a thorough literature review was undertaken to identify the role of citizen's satisfaction as well as the potential obstacles that may influence the adoption rate of e-services and therefore imposing e-services. Moreover, an investigation was conducted by analyzing the e-services provided by three major governmental departments, based on their official WebPages, and classifying them into three categories: mandatory e-services, optional e-services, tangible-optional e-services. This paper argues that the full success of e-services can be accomplished by imposing the optional e-services along with achieving the users' satisfaction and consider it as an indicator for success. The study proposed a conceptual model that addresses the issue of imposing e-services by the governmental departments in Jordan.
Keywords: 650; governmental departments; mandatory e-services; optional e-services; tangible-optional e-services; user satisfaction